Correlation between the policy, media and public agendas in Santiago de Cuba. A longitudinal studio of case - Muñíz Zúñiga, Viviana (2016)
The main purpose of this longitudinal analysis is to determine the correlation between the media agenda of local newspaper Sierra Maestra, as well as the policy and public agendas in the Santiago de Cuba province during 4 periods of time. The main contribution of the paper is that it is the first analysis of its kind in the country, by explaining the relationship between the three agendas in a province during different phases. In addition, an important methodological contribution is presented by combining a quantitative methodology, including Analysis-Synthesis and Induction-Deduction, and techniques such as Content Analysis and Spearman’s ranks Correlation Coefficient. This analysis demonstrates the existence of a moderate correlation and at times a high correlation between the policy agenda and the media agenda, as well as a low or null relationship between the latter and the public agenda. This indicates that socially the Agenda-Setting theory is not met in full at an international level.